SEEING OUR WAY TO FINANCIAL SECURITY, PHYSICAL HEALTH, AND SOCIAL ENGAGEMENT IN THE AGE OF LONGEVITY. (16th November 2018) - Roth, J; Sims, T; Streeter, J; Harrati, A; Vernon, S; Liao, H; Deevy, M; Carstensen, L
Abstract: Sightlines is an ongoing project at the Stanford Center on Longevity that studies how Americans are living healthy, financially secure, and socially engaged lives and investigates how these metrics have changed over time. Here, we present findings on the social engagement and physical health of Americans, but mainly highlight our most recent report on financial security, analyzing the latest trends in this domain over six original Sightlines metrics, as well as closer inspections of financial literacy, homeownership, and retirement preparedness. In this report, we utilize five data sources: the Survey of Consumer Finances, the Health and Retirement Study, the National Longitudinal Survey of Youth, the Consumer Expenditure Survey, and our own nationally representative Milestones survey to analyze financial indicators. In addition, we parse our data by age, ethnicity, education, and gender to discover how well different subsets of Americans are preparing for a healthy, financially secure lifetime. Important findings include: overall, younger generations are falling behind in reaching the same life and financial milestones at the same ages as older adults, Baby Boomers mark when financial preparedness for retirement starts to decline versus older generations, and there are demographics disparities in financial well-being that make the decline uneven across the population, such as lower financial literacy among women versus men. These findings indicate that changes must be made, and we plan to use this knowledge to design improved educational programs and influence policy, so that all Americans can enjoy secure, longer lives.